A clinical audit of responses by an emergency department: medical emergency team, within a 469 bed private hospital in Gauteng, South Africa, from 1st January 2010 to 31st December 2010 - Kotze, Shane (My University, 2016)
Introduction Patients often deteriorate when in hospital, which may result in unscheduled admission to Intensive Care Units, cardiac arrest and possibly death. Medical Emergency Teams (MET) have been instituted in hospitals to mitigate these patient critical events. Aim The aim of this clinical audit was to appraise the practices of a MET in a large, private South African hospital. Method A retrospective, transverse, observational analysis of 278 MET responses (which occurred in 2010) was undertaken. Results Males accounted for 57.2% of MET responses. Males further accounted for 60.9% of cardiac arrests. Females had a higher mortality compared to males. Age analysis showed a multimodal age distribution. A mean overall age of 56.2 years was observed. A paediatric median of 0.583 years was found whilst a mean of 60.432 years was found in the adult category. An increase in frequency of MET responses was observed with advancing age with associated poor outcome. The MET functioned hospital-wide. Intensive care unit (ICU) and high care unit (HCU) areas accounted for the majority of MET responses and cardiac arrest prevalence. Similarly, ICU and HCU areas had a high mortality at the end of MET responses – 33% to 80% mortality. No statistically significant difference in activation frequency occurred between days of the week. No “weekend effect” could be immediately demonstrated. Public holidays proved to be difficult to objectively analyse with regards to prevalence of MET responses. A peak in MET response frequency was demonstrated between 03h00 to 03h59. A minimal increased night-time prevalence was found but was not statistically significant. An increase in mortality was noted for cardiac arrest occurring at night. The prevalence of cardiac arrest was 0.324 per 100 admissions. The return of spontaneous circulation (ROSC) rate for the MET was 62.7%. The cardiopulmonary resuscitation (CPR) survival rate at the end of MET responses was 58.2%. A total of 596 man-hours were expended on MET responses. The average MET response duration was 26 minutes. Conclusion The MET in operation at the Hospital in this audit is a combined MET and Heart Arrest Team. The MET operates hospital-wide, 24 hours a day and is internationally comparable.
A research report presented to the Faculty of Health Sciences, University of the Witwatersrand in partial fulfilment for the degree of Master in Science in Medicine: Emergency Medicine. Johannesburg, November 2015.